The Effect of Circuit Training and Body Mass Index on Aerobic Capacity, Body Fat and Body Circumference in Women Aged 20-45 - Julinar, Nurul (Department of Physical Education, Sport, Health and Recreation, 2022)
The purpose of this study was to analyze the effect of circuit training and body mass index on aerobic capacity, body fat, and body circumference in women aged 20-45. The total sample was 30 women in Bumireso Village including experimental and control groups. The research used purposive sampling with pretest and posttest. Data collection techniques used are questionnaires, food recall, daily activity record booklets, fat calculator software, and documentation. The result data analyzed paired sample T-Test using IBM SPSS Statistic 25.00 for windows. The results obtained circuit training of trekking poles for the normal group increasing in aerobic capacity by 7.92, decreased body fat to -1.68, decreased arm circumference by -1, decreased abdominal circumference by -3.2, and decreased thigh circumference by -0.4 (p = 0.000). The trekking poles group for the overweight group increased aerobic capacity by 4.8, a decrease in body fat of -2.58, a decrease in arm circumference of -1.2, decreased in the abdominal circumference of -2.8, and decreased thigh circumference of -0.8 (p = 0.000). The group without trekking poles in the normal group increased in aerobic capacity by 3.2, a decreased in body fat of -1.58, a decreased in arm circumference of -0.4, decreased in the abdominal circumference of -2.8, and a decreased in thigh circumference of -0.4 (p = 0.000). The group without trekking poles in the overweight group an increase in aerobic capacity of 2.6, decreased body fat of -2.64, a decreased in arm circumference of -1.2, a decreased in the abdominal circumference of -2.8, and a decreased in thigh circumference of -0.6 (p = 0.012). Circuit training using trekking poles is better for increasing aerobic capacity, reducing body fat, and decreasing body circumferences.